Re‐analysis of key evidence in the case for a hemispherically synchronous response to the Younger Dryas climatic event. (7th January 2013) - Green, Helen; Woodhead, Jon; Hellstrom, John; Pickering, Robyn; Drysdale, Russell
Abstract A south‐east Australian speleothem stable isotope record displaying an apparent cooling synchronous with the northern hemisphere Younger Dryas climate event (12.9–11.7 ka) has significantly influenced scientific thinking on the climatic response of the southern hemisphere following the Last Glacial Maximum. This is one of very few records displaying such a response, and yet the cooling was inferred from substantial extrapolation between just three uranium‐series ages. Technological advances since then have produced major improvements in both the spatial resolution and the accuracy of uranium‐series geochronologies. Re‐analysis of this sample has yielded ages of 7.96 ± 0.36 to 7.69 ± 0.33 ka for the interval previously inferred to span the Younger Dryas, and reveals a substantial hiatus in deposition from 6.93 ± 0.64 to 1.83 ± 0.16 ka. These data not only refute the original evidence for an inter‐hemispheric synchroneity of the Younger Dryas but also reject any evidence for neoglacial conditions at 3 ka. Copyright © 2013 John Wiley & Sons, Ltd.